The dynamics of communication in ethnically diverse groups: the experiences of academics - A.Manaf, Aini Maznina (2011)
This article outlines a study of the dynamics of group communication between ethnically diverse members in an academic setting. The study provides an understanding of how ethnic diversity influences communication in small groups of academics. Drawing on in-depth interviews with forty academic researchers from five universities in Malaysia, it is shown that despite little interaction among members of different ethnic backgrounds on non-task activities, the groups were cohesive and their communication climate was supportive; thus emphasising the practices of collaborative decision making, co-operative problem solving and equal participation in the groups. Based on findings that vary somewhat from the literature, the study concludes that ethnic diversity brings a positive outcome to communication in groups.